Winnicott and Ricoeur: Dialogues between concern for other and ethical intentionality - Bareiro, Julieta María (2021)
In this work, we intend to make an articulation between the notion of “concern for the other” and “ethical intent” in P. Ricoeur with those of the development of subjectivity in Winnicott and its relationship with the environment. Through this crossing it can be established that both the maturation processes and the analyst’s place find their foundation in P. Ricoeur’s theory, not only metapsychological, but also ethical.